FROST INVESTIGATION 1944-1945. APPENDIX 5. REPORT ON TRUAX FIELD, MADISON, WISCONSIN. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The purpose of this report is to present the complete results of the investigation performed by the Milwaukee District at Truax Field. The general scope of the investigation included field tests to determine the development of frost in the soil and changes in soil and pavement conditions as a result of the frost; laboratory tests on pavement, base and subgrade materials; and traffic tests during the frost melting period. (Author) See also Appendices 3/4, AD-712 426 and Appendix 6, AD-712 388.